The Nature of Contemporary Conflicts and Prospects for Adapting Collective Security Systems: A Triadic Approach - Natalia I. Kharitonova (Vestnik RUDN. International Relations)
The study focuses on the analysis of the nature of modern conflicts, and the prospects for the adaptation of collective security systems in the context of the emergence of a polycentric world order. The analysis draws upon three key factors: the hybridization of conflict interactions in the modern world, the actualization of the civilizational approach in practical international politics, and the legitimacy more or less inherent in collective actions. The purpose of the study is providing an answer to the question of whether international organizations will continue to play the role of regulators and insurance mechanisms against new global conflicts in the future. The study’s tasks are threefold: first, to characterize the international context that both shapes and reflects changes in the nature of conflict; second, to identify key changes in the nature of modern conflict interactions; third, to determine new requirements for collective security systems in a polycentric world. The parameters of the problem being analyzed are determined by the fact that the nature of conflicts has changed significantly over the past half-century and continues to change, while changes in the basic principles of the existence of international organizations have either not occurred at all or represent rather modest attempts to define acceptable formats for the world community. This discrepancy signifies a pivotal challenge in contemporary world politics, exemplifying systemic transformations within the international relations framework. The methodological framework of the study incorporates a triadic approach, facilitating the identification of intricate characteristics that define specific phenomena. The use of the triadic method in order to determine the characteristics of modern conflicts (by “coupling” the phenomena of strategy, sovereignty and hybridity) and systems of collective security in the context of polycentrism (by “coupling” the phenomena of civilization, collective action and security) made it possible not only to determine the main parameters of changes of the modern conflicts nature in the transition period and the requirements for collective security systems in the new international political conditions. Furthermore, it has facilitated an exploration of future trends in order to outline the contours of new approaches to analyzing the international situation, taking into account the experience of the current global upheavals.